Pengaruh Efektivitas Penagihan Pajak Terhadap Kepatuhan Wajib Pajak Restoran di Badan Pendapatan Daerah Kota Tangerang Selatan - Nurul Fikri Azzahra; Dini Gandini Purbaningrum (Department of Accounting, Faculty of Economics & Business, 2022)
The purpose of this research is to find out how the big Effect of Tax Collection Effectiveness on Restaurant Taxpayer Compliance at the Regional Revenue Agency of South Tangerang City. The method used in this study is a quantitative method. The sampling technique used is purposive sampling. The respondents used were restaurant taxpayers who did not complied in the 2020-2022 period. The effectiveness of tax collection has an effect on Restaurant Taxpayer Compliance, where data is obtained that the value of sig for variable X to variable Y is 0.000. So that 0.000 <0.1 and the calculated T value is 12.707 > the T table value (0.05-98) is 1.661. So it can be concluded that H1 is accepted and H0 is rejected, it’s means that there is an effect of the effectiveness of tax collection on restaurant taxpayer compliance at the Regional Revenue Agency of South Tangerang City.